2018
DOI: 10.1253/circj.cj-18-0279
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of the Preservation of Activities of Daily Living on Post-Discharge Outcomes in Patients With Acute Heart Failure

Abstract: Results demonstrate that low BI at discharge and decreased BI during hospitalization predicted poor outcomes in Japanese patients with acute HF. A comprehensive approach, beginning in the acute phase, aiming to maintain patients' ability to perform activities of daily living could provide better management of HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
2
34
1
Order By: Relevance
“…[2][3][4][5] When such patients are hospitalized with acute HF, restricted mobilization and prolonged bed rest for the treatment or due to the congestive symptoms are likely to cause physical deconditioning, which leads to further impairment in ADL. 6 Indeed, according to recent large-scale registry data, early ambulation of HF patients is associated with a reduction in the length of hospital stay and HF readmission rate. 7 Thus, minimizing the length of hospital stay is encouraged in the clinical guidelines for the…”
mentioning
confidence: 99%
“…[2][3][4][5] When such patients are hospitalized with acute HF, restricted mobilization and prolonged bed rest for the treatment or due to the congestive symptoms are likely to cause physical deconditioning, which leads to further impairment in ADL. 6 Indeed, according to recent large-scale registry data, early ambulation of HF patients is associated with a reduction in the length of hospital stay and HF readmission rate. 7 Thus, minimizing the length of hospital stay is encouraged in the clinical guidelines for the…”
mentioning
confidence: 99%
“…We have previously demonstrated that hospitalization for HF was signi cantly correlated with decreased BI as an assessment of ADL, and a decreased BI during hospitalization was associated with worse clinical outcomes [8]. It has also been reported that a decline in ADL due to acute HF is an independent risk factor of hospitalization for HF and mortality [33].…”
Section: Discussionmentioning
confidence: 97%
“…The BI was obtained by ward nurses at admission and at discharge, as previously reported [8]. Changes in the BI were calculated as the difference between the BI on admission and the BI on discharge.…”
Section: Assessments For Geriatric Conditionsmentioning
confidence: 99%
“…The Barthel Index (BI) is one of the most commonly used methods to assess a person's basic self-care ability and the intensity of care required; this measure is better suited to acute settings [24][25][26]. If the total score is greater than 40, the patient is considered more capable.…”
Section: Secondary Outcome Measurements Activities Of Daily Living Bamentioning
confidence: 99%